Pengaruh Content Creator, Online Customer Review Dan Product Avaibility Terhadap Buying Decision (Studi Kasus pada Konsumen Brand Ventela di Kota Malang) - Edi, Dhadhun Arief Sarwo; Nurhajati, Nurhajati; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study investigates the influence of content creators, online customer reviews, and product avaibility simultaneously and partially on purchasing decisions for Ventela brand shoes among consumers in Malang City. This study uses a quantitative approach with a survey method. Data were collected from 75 respondents who are Ventela consumers in Malang City through questionnaires distributed online. The data analysis technique used is multiple linier regression analysis. The results of the study are expected to reveal how much contribution each independent variable (content creator, online customer reviews, and product availability) has in influencing Ventela consumer purchasing decisions. The implications of this study are expected to be valuable input for Ventela companies in developing more effective and responsive marketing strategies to consumer preferences in this digital era. Keywords:Content Creator, Online Customer Review, Product Avaibility, Buying Decision